Sosialisasi Pembentukan Badan Usaha Milik Desa Sebagai Upaya dalam Meningkatkan Kesejahteraan Masyarakat Desa Parumasan - Ahmad Fatoni (Yayasan Pendidikan Penelitian Pengabdian Algero, 2023)
Community service in the form of socialisation of the formation of Village-Owned Enterprises (BUMDes) in Parumasan Village, Cipeucang District, Pandeglang Regency, Banten Province. The methods of community service are lectures, questions and answers, and discussions. The lecture method provides basic information, the question and answer method provides opportunities for clarification, and the discussion method allows participants to actively participate in developing their understanding and contributing new ideas. Thus, the community has a better chance to understand, support, and be actively involved in the development of BUMDes in their village. The objective of this socialisation is to increase the knowledge and awareness of the village community on the benefits of BUMDes in improving their welfare. The outcome of the socialisation encourages active community participation in the ownership and management of the BUMDes, so that it does not only belong to the village apparatus, but also to the entire village community. In addition, village officials and the community were also involved in the preparation of the BUMDes organisational structure. With this socialisation, it is hoped that the Parumasan village community can better understand the important role of BUMDes in local economic development and improving their own welfare.